2012
DOI: 10.4314/bcse.v26i1.6
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of oils and nutrient contents of <i>Nigella sativa</i> Linn. and <i>Trigonella foenum-graecum</i> seeds

Abstract: ABSTRACT. The core objective of this research was to determine the oil characteristics and nutrient contents of Nigella sativa and Trigonella foenum-graecum seeds. Characteristics of seed oils revealed higher degree of unsaturation and as determined by gas liquid chromatography (GLC) reported herein the major unsaturated fatty acids were linoleic acid (52.6% in N. sativa and 42.5% in T. foenum-graecum), followed by oleic acid (23.5% in N. sativa and 20% in T. foenum-graecum), while the main saturated fatty aci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 17 publications
(20 reference statements)
0
15
0
1
Order By: Relevance
“…This effectiveness may be because of a combination of fatty acids (85% unsaturated fatty acids), volatile oils and trace elements (Cheikh et al, 2007). Abbas et al (2012) found that the fatty acid patterns of nigella sativa seed oil were qualitatively similar to those of other plants; the essential fatty acid linoleic (52.6%) being the major fatty acid, followed by oleic acid (23.5%). Linolenic acid was detected in small quantities in samples.…”
Section: Discussionmentioning
confidence: 73%
“…This effectiveness may be because of a combination of fatty acids (85% unsaturated fatty acids), volatile oils and trace elements (Cheikh et al, 2007). Abbas et al (2012) found that the fatty acid patterns of nigella sativa seed oil were qualitatively similar to those of other plants; the essential fatty acid linoleic (52.6%) being the major fatty acid, followed by oleic acid (23.5%). Linolenic acid was detected in small quantities in samples.…”
Section: Discussionmentioning
confidence: 73%
“…Elmnan, Balgees, and Mangara () reported that fenugreek seed contained 28.60% protein, 14.04% crude fiber, 6.16% ether extract, and 4.65% ash. Abbas Ali et al () reported that T. foenum‐graecum seed contained 28% protein. It was shown partly differences between results to literature values as stated above.…”
Section: Resultsmentioning
confidence: 99%
“…Trigonella foenum‐graecum (fenugreek; Leguminoseae family) is an annual herb (Abbas Ali et al, ). It is generally used as a traditional spice (Petit et al, ; Taylor, Elder, Chang, & Richards, ).…”
Section: Introductionmentioning
confidence: 99%
“…Habbatussauda atau jintan hitam (Nigella sativa L.) adalah tanaman aromatik semusim, merupakan tanaman obat potensial dan telah digunakan di banyak negara termasuk India, negara-negara Arab, dan Eropa tidak hanya sebagai bumbu dan perasa, tetapi juga sebagai bahan obat (Hamid, 2012). Bijinya merupakan sumber natrium, kalsium, kalium, dan zat-zat lain yang berperan dalam kesehatan (Abas-Ali et al, 2012). Tanaman ini dibudidayakan di wilayah mediteranean dan berkembang di berbagai wilayah termasuk India dan Pakistan (Abdolrahimi et al, 2012).…”
Section: Pendahuluanunclassified